Histologic Characteristics of the Fetal Inflammatory Response Associated with Neurodevelopmental Impairment and Death in Extremely Preterm Infants - Salas, Ariel A (2013)
To test the hypothesis that increasing severity of the fetal inflammatory response would have a dose-dependent relationship with severe neurodevelopmental impairment (NDI) or death in extremely preterm infants. STUDY DESIGN: We report 347 infants 23 to 28 weeks gestational age admitted to a tertiary neonatal intensive care unit between 2006 and 2008. The primary outcome was death or NDI at 18–22 month follow-up. Exposure status was defined by increasing stage of funisitis (stage 1: phlebitis; stage 2: arteritis with or without phlebitis; stage 3: subacute necrotizing funisitis) and severity of chorionic plate vasculitis (inflammation with or without thrombosis). RESULTS: A fetal inflammatory response was detected in 110 placentas (32%). Severe NDI/death rate was higher in infants with subacute necrotizing funisitis compared with infants without placental/umbilical cord inflammation (60% vs. 35%; p<0.05). Among infants with stage 1 or 2 funisitis, the presence of any chorionic vasculitis was associated with higher rates of severe NDI/death (47% vs. 23%; p<0.05). After adjustment for confounding factors, only subacute necrotizing funisitis (RR: 1.87; 95% CI: 1.04 – 3.35; p=0.04) and chorionic plate vasculitis with thrombosis (RR: 2.21; 95% CI: 1.10 – 4.46; p=0.03) were associated with severe NDI/death. CONCLUSIONS: Severe fetal inflammatory response characterized by subacute necrotizing funisitis and severe chorionic plate vasculitis with thrombosis are associated with severe NDI/death in preterm infants.